Reconstructing Meat Consumption through Biomarker Analyses of Paleofeces - Jenna M. Battillo; Abigail E. Fisher (Ethnobiology Letters, 2015)
This mini-review outlines three underutilized approaches for studying meat-based biomarkers in archaeological paleofeces that we expect will increase in significance within the field. Myoglobin, stable isotope, and aDNA analyses all have untapped potential to inform meat-based dietary constituents.